Calcineurin Inhibitors Downregulate HNF-1β and May Affect the Outcome of HNF1B Patients After Renal Transplantation. Issue 9 (September 2016) - Faguer, Stanislas; Esposito, Laure; Casemayou, Audrey; Pirson, Yves; Decramer, Stéphane; Cartery, Claire; Hazzan, Marc; Garrigue, Valérie; Roussey, Gwenaelle; Cointault, Olivier; Ho, Thien; Merville, Pierre; et al.
Abstract : Background: Patients with HNF1B mutations develop progressive chronic renal failure, diabetes mellitus (40-50%), and liver tests abnormalities (40-70%). In HNF1B patients who reach end-stage renal disease, single kidney transplantation (SKT) or combined kidney-pancreas transplantation can be considered. Methods: A retrospective multicenter study including 18 HNF1B patients receiving SKT or kidney-pancreas transplantation, and in vitro experiments including the characterization of the HNF1B expression after calcineurin inhibitor (CNI) exposure. Results: After SKT, 50% of the HNF1B patients develop early posttransplantation diabetes mellitus, whereas 40% experience new-onset or severe worsening of preexisting abnormalities of liver tests, including severe cholestasis. In liver biopsies, disorders of the cholangiocytes primary cilium and various degrees of bile duct paucity and dysplasia were identified. In vitro studies combining CNI exposure and siRNA-mediated inhibition of NFATc revealed that calcineurin inhibition decreases HNF1B expression in epithelial cells but independent of NFATc . Conclusions: Because HNF1B -related disease is a heterozygous condition, CNIs used to prevent rejection may induce reduced expression of the nonmutated allele of HNF1B leading to a superimposed defect of HNF-1β transcriptional activity. Taking into account the specific risk of posttransplantation diabetes mellitus and liver disorders in HNF1B patients, these findings advocate for in-depth characterization of pathways that regulate HNF1B and plead for considering individually tailored graft management that may include a CNI-free immunosuppressive regimen. Interventional studies will have to confirm this individualized approach. Abstract : After kidney transplantation, 50% of patients with HNF1β mutations develop posttransplant diabetes mellitus and 40% have liver tests abnormalities. The authors discuss the role of cyclosporine as a blocker of HNF1β and test this hypothesis in in vitro experiments. Supplemental digital content is available in the text.